Securing m-government transmission based on symmetric and asymmetric algorithms: A review - Watari M.A.; Zaidan A.A.; Zaidan B.B. (2023)
Several changes have taken place in the field of communication technologies (ICT) in recent years, specifically in the era of rapid technology development. Mobile technologies, especially smart phones, have replaced computers in various significant tasks. This development influenced the interactions between citizens and government agencies in m-Government. m-Government is an extension of e-Government, which provides services to citizens in general or to subscribers in particular. These services range from public to private bodies and the data transmitted sometimes require authentication and confidentiahty. Thus, the need for data security is inevitable. This study will discuss the security of m-Government using security algorithms and report some literature work in this field to highlight its weaknesses. 2013 Asian Network for Scientific Information.